Development of generic gliclazide 60 mg modified release tablets using central composite design - Elsayed, Tarek Mohamed Ali; Mandal, Uttam Kumar; Kasmuri, Abdul Razak (College of Pharmacists of Buenos Aires Province, Argentina, 2015)
A modified release gliclazide 60 mg tablet using Methocel® K100 Premium LV DC2 as a drug retaining polymer was prepared by direct compression. Central composite design was adopted for formulation optimization. The two independent formulation variables included the amount of Methocel® K100 LV DC2 and Maltrin® M150, whereas the response variables were cumulative % drug release in 1, 2, 4, 8, and 12 h. Drug release data were fitted to various mathematical models for describing the release mechanism from tablets. The effect of polymer and maltodextrin content on gliclazide release at different time points were statistically evaluated by applying one-way ANOVA at 0.05. Four more formulas were prepared to evaluate the prediction ability of the model. All the formulations showed a high correlation coefficient (r2) with zero order and Korsmeyer-Peppas release mechanism. The actual cumulative % drug release versus predicted of the evaluation formulations showed good model prediction with high similarity (86-98) and low difference factors (1-3).